Communication between the nursing staff and relatives of patients in the intensive care unit - Kaisy Pereira Martins; Laura Cristhiane Mendonça Rezende; Kátia Neyla Freitas Macedo Costa; Tatiana Ferreira Costa (Universidad de Alicante, 2014)
The intensive care unit (ICU) is an environment in which the technique is more aspects of care. In this perspective, it is important to use communication in nursing, awakening a bond of trust between family and professional. Given this reality aimed to analyze the communication between the nursing staff and the relatives of ICU patients. The descriptive is qualitative approach in the ICU of a teaching hospital. Participants were thirty families of ICU patients. Data were collected through semi-structured interviews in September 2011 and analyzed using content analysis. It was found that family members do not receive nursing guidelines on the environment and health of the patient, and also does not provide time to interact during visits. Thereby the emerging need to encourage the training of these professionals to the conscious use of communication.